Titania nanoparticles synthesis in mesoporous molecular sieve MCM-41 - Lihitkar, N. B.; Abyaneh, Majid Kazemian; Samuel, V.; Pasricha, R.; Gosavi, S. W.; Kulkarni, S. K. (Journal of Colloid and Interface Science, 2007)
Nanocrystalline titanium oxide (TiO2) is one of the most useful oxide material, because of its widespread applications in photocatalysis, solar energy conversion, sensors and optoelectronics. The control of particle size and monodispersity of TiO2 nanoparticles is a challenging task. The use of MCM-41, an inorganic template of uniform pore size (2-10 nm), can overcome this difficulty and produce stable nanoparticles of uniform size and shape. Here, we demonstrate the synthesis of titania nanoparticles inside the pores of silica based MCM-41 forming a TiO2/Si-MCM composite. Composites are formed in the alcoholic medium by incipient wetness impregnation method. Titania particles of average 3 nm size are obtained. Effect of silica and titania precursors on the quality of nanoparticles has been investigated. The characterization of titania-MCM-41 composites has been carried out using a variety of techniques like UV-vis absorption spectroscopy, X-ray diffraction, FT-IR spectroscopy, X-ray photoelectron spectroscopy, transmission electron microscopy and photoluminescence spectroscopy. It has been found that the titania particles are co-ordinated with Si-MCM by Si-O-Ti covalent bond. (C) 2007 Elsevier Inc. All rights reserved.
Keywords: incipient wetness impregnation; Mesoporous material; template; titania

Optical investigations of interaction between zinc tetra phenyl porphyrin and CdSe nanoparticles - Lihitkar, N. B.; Singh, S. B.; Singh, Jai; Srivastava, O. N.; Naik, R. H.; Kulkarni, S. K. (Chemical Physics Letters, 2009)
Interactions between nanoparticles of zinc tetra phenyl porphyrin (ZnTPP) with CdSe nanoparticles in dimethyl sulphoxide solvent have been investigated. A ZnTPP-CdSe complex was formed which showed substantial changes in the UV-Vis absorption spectra in the presence of CdSe. Fluorescence measurements showed an interesting behavior at low as well as high concentrations of CdSe. When low concentrations of CdSe nanoparticles were added to the ZnTPP nanoparticles solution, besides two fluorescence bands due to ZnTPP nanoparticles, an intense new band appeared. On the other hand at high concentrations of CdSe one of the fluorescence band of ZnTPP at similar to 604 nm increased. (C) 2009 Published by Elsevier B. V.